Application of K-Means Clustering Algorithm in Edam Burger Sales Information System for Inventory Control Optimization - Muhammad Rofiq Ubaidillah; R Wisnu Prio Pamungkas; Prio Kustanto (Ninety Media Publisher, 2026)
Manual sales and inventory management in small culinary enterprises often leads to data inaccuracies, stock mismanagement, and underutilized transactional data. This study aims to design a web-based sales information system integrated with the K-Means clustering algorithm to optimize inventory control at Edam Burger & Frozen Foods. Utilizing the Waterfall methodology, the system was developed using the Laravel framework and MySQL. The analytical engine processed five months of transactional data across fifteen products, applying Min-Max Normalization to equalize the scales of sales volume, revenue, and transaction frequency. The K-Means algorithm successfully segmented the product catalog into three distinct categories based on performance: one high-selling core product (6.7%), three medium-selling secondary items (20%), and eleven low-selling complementary products (73.3%). Black Box Testing confirmed a 100% functional success rate across all system modules. The primary novelty of this research lies in seamlessly embedding the K-Means engine directly into the operational dashboard, overcoming the common barrier of offline, standalone data mining. This integration enables real-time, data-driven procurement strategies, providing actionable recommendations: prioritizing continuous stock availability for high-demand items, scheduling regular restocking for medium items, and minimizing capital tied up in low-moving inventory to reduce food waste. Ultimately, this integrated approach empowers small business owners to transition from intuition-based management to systematic, algorithm-driven inventory optimization. This study successfully bridges the gap between routine transactions and strategic analytics.